2006
DOI: 10.4049/jimmunol.177.3.1925
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Stimulation of Intrinsic Renal Cells in the Induction of Immune-Mediated Glomerulonephritis

Abstract: Infection may exacerbate organ-specific autoimmune disease such as glomerulonephritis. This may occur in the absence of a measurable effect on the adaptive immune response, and the mechanisms responsible are not fully understood. To investigate this, we have studied the effect of TLR2 ligation by the synthetic ligand Pam3CysSK4 on the development of glomerulonephritis in mice. We demonstrated that glomerular inflammation induced by passive administration of nephrotoxic Ab does not occur in the absence of TLR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 32 publications
2
28
0
3
Order By: Relevance
“…Early reports showed that a small dose of endotoxin could exacerbate the heterologous phase in the rat [17]. Our own studies extended these findings using specific ligands for TLR2 or TLR4, given with glomerular binding antibody [3, 4]. Bone marrow chimera experiments showed that there was an important role for TLR2 or TLR4 on renal cells in addition to neutrophils.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Early reports showed that a small dose of endotoxin could exacerbate the heterologous phase in the rat [17]. Our own studies extended these findings using specific ligands for TLR2 or TLR4, given with glomerular binding antibody [3, 4]. Bone marrow chimera experiments showed that there was an important role for TLR2 or TLR4 on renal cells in addition to neutrophils.…”
Section: Introductionsupporting
confidence: 63%
“…Primary cultures of mouse renal tubular epithelial cells express TLR1–TLR4 and TLR6 [1]. Cultured mouse mesangial cells show this same pattern of TLR expression [2,3,4]. These studies on cultured cells are of value, but of more interest is TLR expression in vivo, as demonstrated on intact tissue sections.…”
Section: Introductionmentioning
confidence: 99%
“…Still, glomerular inflammation in heterologous anti-GBM disease involves innate rather than adaptive immunity given that the model was MyD88- but not Rag2-dependent. Since injury in this model was previously shown to involve TLR2 and TLR4 [33], [34] we assume that the TLR2/MyD88 and the TLR4/MyD88 pathways predominate for the induction of innate immunity in this model of acute glomerulonephritis.…”
Section: Discussionmentioning
confidence: 98%
“…Both have been shown to affect the course of glomerulonephritis, although these studies involved exogenous administration of ligands [23,24]. Both TLR2 and TLR4 have also been shown to mediate renal injury following ischaemia/reperfusion [25,26,27].…”
Section: Discussionmentioning
confidence: 99%